Niklas Luhmann and Economics - Иван Алексеевич Болдырев (Journal of Economic Sociology, 2011)
The paper considers economic ideas of Niklas Luhmann (1927–1998) who was one of the leading social theorists of the 2nd half of the 20th century. The author looks at Luhmann’s account of the economy as a social system (proposed in the 1970–1980s) in the context of the evolution and methodological issues of modern economics. He shows, first, which of the Luhmann’s ideas are relevant for kеу modern approaches in economics and, second, what is specific about Luhmann’s economic thinking.экономика как социальная система